Divergent responses of soil carbon and nitrogen pools to short-term nitrogen addition between two plantations in Northeast China - Li, Yedong; Wang, Bo; Dou, Sen; Shen, Haoyue; Mei, Liyong; Zhang, Yang; Zeng, Ximing; Zhang, Yaya; Pei, Yameng; Ren, Haoye; Wu, Shimin (International Journal of Agricultural and Biological Engineering, 2019)
Nitrogen (N) deposition has a profound influence on forest soil carbon (C) and N pools, but there was no consensus on the responses of different C and N components in different forest types. In this study, a two-year simulated N deposition experiment with four levels of N (NH4NO3)-addition treatments (0, 50, 100, and 150 kg N/hm2·a) were conducted in Larix gmelinii (LG) and Quercus mongolica (QM) plantation in Northeast China, in order to investigate the C and N pool dynamics under continuously enhanced N deposition. Soil organic carbon (SOC), soil total N (STN) and their active components (readily oxidizable C, ROC; dissolved organic C, DOC; microbial biomass C, MBC, dissolved organic N, DON; microbial biomass N, MBN) of the forest soil were measured monthly from May to October 2017. C and N contents in LG were observed higher than in QM. N addition had no effect on SOC and STN of LG, but significantly increased SOC and STN of QM at low N addition level. Low N addition generally raised active C components (ROC, DOC, and MBC) in both plantations, whereas high N addition did not significantly affect these components, or even decreased ROC in LG soil. Low N addition also increased STN and MBN of QM, while no significant change in STN and MBN of LG was observed. DON was directly affected by N addition and increased significantly with elevated N addition levels. The results indicated that N addition, especially of low rate, might enhance the C sequestration capacity of the forest soils and mitigate climate change.Keywords: nitrogen deposition, forest soil, active carbon, active nitrogenDOI: 10.25165/j.ijabe.20191206.5266Citation: Li Y D, Wang B, Dou S, Shen H Y, Mei L Y, Zhang Y, et al. Divergent responses of soil carbon and nitrogen pools to short-term nitrogen addition between two plantations in Northeast China. Int J Agric & Biol Eng, 2019; 12(6): 82–90.